PENGARUH KONSENTRASI SUKROSA PADA FERMENTASI SARI BUAH PEPAYA (Carica papaya L) - Paendong, Yunita R.; Ludong, Maya M.; Koapaha, Teltje (Jurnal Teknologi Pertanian (Agricultural Technology Journal), 2021)
Utilization of the hawaiian papaya fruit or the local name “bird papaya” which is processed into fermented drinks (fruit wine) is one way to increase the added value and usefulness of the papaya fruit. One of the alternative processing technologies for papaya fruit by cooking